English Dies used in the Scandinavian Imitative Coinages - Blackburn, Mark (Hikuin, 1985)
The suggestion that certain of the dies used to strike the Scandinavian imitative coinages of the late tenth and early eleventh centuries were official dies removed from English mints was first made in 1961 in two pioneering studies, one concerned with coins of iEthelred H’s Crux and Intermediate Small Cross (‘ISC’) types, and the other a variety of issues mostly of the late 1010s and 1020s. Each applied the techniques of die analysis and stylistic analysis - which had been used so effectively in the Anglo-Saxon series - to show that coins which had for long been accepted as English were in fact imitations. A number of diechains (groups of die-linked coins) were constructed containing improbable combinations of mints and types or coins of barbarous workmanship. These chains drew primarily on the systematic collection of Anglo-Saxon coins in Stockholm (that published by B. E. Hildebrand) and so consisted of reasonably literate specimens, though most of them could be extended further into the blundered series of coins kept in the Scandinavian cabinets at Stockholm. Most of the imitations of jEthelred’s and Cnut’s coins including those in these die-chains are generally regarded as Scandinavian, none so far as we know has been found in Britain and, as we shall see, the scale of the operation indicated by the larger diechains suggests that there was one or more major mints producing anonymous imitations in southern Scandinavia (i.e. Denmark), which rivalled Sigtuna in central Sweden.